In situ construction of a 2D CoTiO3/g-C3N4 photocatalyst with an S-scheme heterojunction and its excellent performance for CO2 reduction. Issue 21 (29th September 2022) - Huang, Haohui; Liu, Xingqiang; Li, Fang; He, Qingyun; Ji, Hongbing; Yu, Changlin
Abstract : The CoTiO3 /g-C3 N4 heterojunction showed a stronger redox potential than g-C3 N4 . Furthermore, the use of triethanolamine as a h + /–OH and e − sacrificial agent significantly enabled the efficient utilization of photogenerated electron–hole pairs. Abstract : To address the high combination rate and low reductive oxidation capacity of photogenerated electron–hole pairs in photocatalysts, the synthesis of S-scheme heterojunction photocatalysts is considered as an effective strategy to improve the photocatalytic performance. In this work, 2D CoTiO3 /g-C3 N4 (CTO/CN) photocatalysts with an S-scheme heterojunction were prepared by in situ growth of CoTiO3 nanoparticles onto 2D porous g-C3 N4 nanosheets. Compared with the pure g-C3 N4, CTO/CN catalysts with different CTO contents exhibit excellent photocatalytic CO2 reduction performance under visible light illumination. The unique band alignment of S-scheme heterojunctions not only suppresses the recombination of photogenerated electron–hole pairs but also produces a sufficient photovoltage to drive the CO2 reduction reaction. Among them, the 2.0% CTO/CN sample exhibits the best photocatalytic activity for CO2 reduction to CO (at a rate of 236.2 μmol g −1 h −1 ) and H2 (at a rate of 75.2 μmol g −1 h − ) 1 which were 229.3 and 221.2 times higher than those of pure g-C3 N4 . Meanwhile, the 2.0% CTO/CN sample exhibits excellent photocatalytic stability during the photocatalytic CO2 reduction cycle reaction. This work provides a new insight into the design of S-scheme heterojunction photocatalysts for photocatalytic CO2 reduction.